Membros: v. 11, n. 2 (2013) - .., .. (RENOTE, 2013)
Editora da Edição Especial Rosane Aragón, Universidade Federal do Rio Grande do Sul (UFRGS) Comitê Editorial da Edição Especial Alberto Castro Nogueira de Castro Junior, Universidade Federal do Amazonas (UFAM) Ana Vilma Tijiboy, Universidade Federal do Rio Grande do Sul (UFRGS) Carla Cristina Burigo, Universidade Federal de Santa Catarina (UFSC) Cleci Maraschin, Universidade Federal do Rio Grande do Sul (UFRGS) Debora Pereira Laurino, Universidade Federal de Rio Grande (FURG) Eliana Rela, Universidade de Caxias do Sul (UCS) Gilda Helena Bernardino de Campos, Pontifícia Universidade Católica do Rio de Janeiro (PUC – Rio) José Aires de Castro Filho, Universidade Federal do Ceará (UFC) Katia Morosov, Universidade Federal de Mato Grosso (UFMT) Lea da Cruz Fagundes, Universidade Federal do Rio Grande do Sul (UFRGS) Marcus Vinícius de Azevedo Basso, Universidade Federal do Rio Grande do Sul (UFRGS) Maria Elisabette Prado, Universidade Bandeirante de São Paulo (UNIBAN) Mauro Pequeno, Universidade Federal do Ceará (UFC) Mara Lúcia Carneiro, Universidade Federal do Rio Grande do Sul (UFRGS) Miriam Struchiner, Universidade Federal do Rio de Janeiro (UFRJ) Orivaldo de Lira Tavares, Universidade Federal do Espírito Santo (UFES) Silvia Bustamante, Universidade católica de Petrópolis (UCP) Simão Pedro Marinho, Pontifícia Universidade Católica de Mina Gerais (PUC Minas) Suely Scherer, Universidade Federal de Mato Grosso do Sul (UFMS)